Detection of EBV DNA in clinically ill patients from 2013 to 2023 in Beijing, China - Su, Ze; Wang, Ziran; Yi, Jie; Chen, Yu; Zhang, Han; Zhang, Dong; Kong, Lingjun; Du, Juan; Yang, Qiwen; Zhang, Rui; Liu, Yali (Frontiers in Microbiology, 2025)
ObjectiveTo investigate the epidemiological characteristics and infection patterns of Epstein–Barr virus (EBV) among patients at Peking Union Medical College Hospital (PUMCH) between 2013 and 2023, with a concurrent analysis of the clinical manifestations and laboratory parameters observed in patients diagnosed with EBV-associated infectious mononucleosis (IM).MethodsA retrospective analysis was conducted on data from 76,135 patients who underwent EBV DNA testing at Peking Union Medical College Hospital between 2013 and 2023. Additionally, clinical data from 152 patients diagnosed with IM from 2013 to 2024 were collected, with their clinical manifestations and laboratory parameters thoroughly evaluated.ResultsThe overall EBV DNA positivity rate was 6.77%, with significant variations observed across different years and age groups. The detection rate of EBV DNA in males was significantly higher than in females, with the highest detection rate observed in individuals aged over 71 years. A decline in EBV DNA detection frequency was noted during the post-COVID-19 pandemic period (2020–2023). Among EBV-related clinical entities, the highest EBV DNA positive rate (37.4%) was observed in patients with IM. In this cohort, liver function abnormalities were common: elevations of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) by 1- to 5-fold above the upper limit of normal were present in 61 (57%) and 41 (59%) cases, respectively. Immunophenotypic analysis revealed a marked increase in the CD8 + DR+/CD8 + ratio in 67 patients (99%), accompanied by a reduction in CD19 + B-lymphocyte percentage in 62 cases (90%), indicating pronounced immune activation and B-cell suppression characteristic of acute EBV infection.ConclusionThe positive rates of EBV DNA showed sex differences and significant fluctuations between 2013 and 2023, without displaying a consistent upward trend. Persistent surveillance and heightened clinical awareness (laboratory parameters, such as ALT, AST and CD8 + DR+/CD8+) are warranted, particularly regarding IM attributable to EBV.